2023
DOI: 10.2188/jea.je20210117
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Mode of Delivery and Postpartum Depression: The Japan Environment and Children’s Study (JECS)

Abstract: Background: Postpartum depression (PPD) has been associated with adverse health outcomes including maternal suicide. Mode of delivery has been suggested to be a risk factor for PPD, but no large cohort study has examined the association between mode of delivery and PPD. We aimed to examine the association between mode of delivery and risks of PPD at 1 and 6 months after childbirth. Methods:In a nationwide study of 89,954 mothers with a live singleton birth, we examined the association between mode of delivery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
0
12
1
Order By: Relevance
“…No apparent relationship between elective and PPD doctor visits was observed for the group of women with depression. Interestingly, our finding is somewhat different from the evidence by Henderson and Quenby [ 33 ], who concluded that women with depression following elective CS have a lower risk of PPD.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…No apparent relationship between elective and PPD doctor visits was observed for the group of women with depression. Interestingly, our finding is somewhat different from the evidence by Henderson and Quenby [ 33 ], who concluded that women with depression following elective CS have a lower risk of PPD.…”
Section: Discussioncontrasting
confidence: 99%
“…Conversely, Eckerdal et al [ 5 ] confirmed that mode of delivery has no direct effect on PPD, but a negative delivery experience mediates an indirect association between clinical CS and PPD. Women who had antenatal psychological distress and underwent CS delivery may be regarded as a target for monitoring PPD [ 33 ]. Since a history of depression is proven to be correlated with postpartum mental health, it is logical to consider the history of depression as an important risk factor when further investigating the relationship between mode of delivery and PPD.…”
Section: Introductionmentioning
confidence: 99%
“…There were 14 cohort studies and 4 case-control studies, with the sample size ranging from 60 to 511,422 participants. Specifically, eleven studies ( 11 , 24 , 26 30 , 32 , 35 37 ) had <10,000 participants, while the remaining seven studies ( 21 23 , 25 , 31 , 33 , 34 ) had >10,000 participants. Furthermore, ten studies ( 21 , 23 , 26 , 28 31 , 34 , 36 , 37 ) were conducted in Asia, whereas seven studies ( 22 , 24 , 25 , 27 , 32 , 33 , 35 ) were carried out in Europe, one studies ( 11 ) were conducted in North America.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, eleven studies ( 11 , 24 , 26 30 , 32 , 35 37 ) had <10,000 participants, while the remaining seven studies ( 21 23 , 25 , 31 , 33 , 34 ) had >10,000 participants. Furthermore, ten studies ( 21 , 23 , 26 , 28 31 , 34 , 36 , 37 ) were conducted in Asia, whereas seven studies ( 22 , 24 , 25 , 27 , 32 , 33 , 35 ) were carried out in Europe, one studies ( 11 ) were conducted in North America. Additionally, ten studies ( 11 , 23 , 24 , 27 30 , 34 , 35 , 37 ) utilized the Edinburgh Postnatal Depression Scale (EPDS) to measure PPD levels, two studies ( 22 , 25 ) deployed the SCL-90, two studies ( 21 , 31 ) adopted the 2010 LNHID, one study ( 26 ) used the CES-D, one study ( 36 ) employed the NHIS-NSC, one study ( 32 ) utilized the BDI, and one study ( 33 ) incorporated the HDR.…”
Section: Resultsmentioning
confidence: 99%
“…CS may increase the risk of maternal and neonatal morbidity and lead to waste of human and financial resources ( 12 ). Currently, it is believed that CS and emergency CS are associated with the increased risk of PPD ( 8 , 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%